2017
DOI: 10.3892/mmr.2017.7302
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA colon cancer associated transcript-1 promotes the proliferation, migration and invasion of cervical cancer

Abstract: Previous studies have revealed significant roles for long noncoding RNA (lncRNA) in the tumorigenesis, metastasis and invasion of various tumors, including cervical cancer. The present study aimed to investigate the potential roles of lncRNA colon cancer associated transcript 1 (CCAT1) in the metastasis and invasion of cervical cancer, and to reveal the potential underlying mechanism. The mRNA expression of lncRNA CCAT1 in cervical cancer tissue was measured using the reverse transcription‑quantitative polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Convincing evidence elucidates the crucial functions and underlying molecular mechanisms of lncRNAs in the physiological and pathological processes of numerous malignancies, including cervical cancer. For instance, depletion of lncRNA colon cancer associated transcript 1 (CCAT1) has been shown to suppress cervical cancer cell viability and migratory and invasive abilities (Jia, Zhang, Tian, Chu, & Xin, ). Silencing of lncRNA steroid receptor RNA activator (SRA) in cervical cancer cell lines impaired cell proliferation, migration and invasion by downregulating epithelial‐to‐mesenchymal transition‐related genes (Eoh et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Convincing evidence elucidates the crucial functions and underlying molecular mechanisms of lncRNAs in the physiological and pathological processes of numerous malignancies, including cervical cancer. For instance, depletion of lncRNA colon cancer associated transcript 1 (CCAT1) has been shown to suppress cervical cancer cell viability and migratory and invasive abilities (Jia, Zhang, Tian, Chu, & Xin, ). Silencing of lncRNA steroid receptor RNA activator (SRA) in cervical cancer cell lines impaired cell proliferation, migration and invasion by downregulating epithelial‐to‐mesenchymal transition‐related genes (Eoh et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of CCAT1 expression inhibited DEX‐mediated protection against OGD/R‐induced cell injury, while overexpression of CCAT1 expression enhanced the Dex‐mediated protection against OGD/R‐induced cell injury. Numerous studies have shown that CCAT1 acts as an oncogene, and is highly expressed in many malignancies, such as colorectal, gastric, ovarian, breast, gallbladder, hepatocellular carcinoma, and lung cancer (Cao et al, ; Gao et al, ; Jia et al, ; Li et al, ; Zhang et al, ; Zhang and Hu, ). CCAT1 exerts its carcinogenic effect by promoting cell invasion and metastasis (Zhao et al, ) and this has been widely studied (Zeng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA colon cancer‐associated transcript‐1 (lncRNA CCAT1) promotes cell invasion and proliferation and thus plays important roles in the malignant transformation of a variety of tumor tissues. The abnormal levels of CCAT1 are thus, potential markers of tumor prognosis, typically predicting adverse clinical outcomes (Cao et al, ; Gao et al, ; Jia et al, ; Li et al, ; Zhang and Hu, ; Zhang et al, ). However, it is not known if a change in CCAT1 expression occurs in hepatocytes during hepatic ischemia reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer-associated transcript1 (CCAT1) serves as a lncRNA involved in regulating the metastatic ability of various cancers via distinct or similar mechanisms, including colon cancer [ 87 ], cervical cancer [ 88 ], hepatocellular carcinoma [ 89 ] and melanoma [ 90 ] etc. Zhuang et al first uncovered the metastasis-related functions of CCAT1 in HNC.…”
Section: Other Tumor Metastasis-suppressing Lncrnasmentioning
confidence: 99%